Proverbs: pathways to wisdom - Hernández, Dominick S. (Abingdon Press, 2020)
"There is a lot of talk these days about "the good life." It's not a new topic-the book of Proverbs talked about just that. Its sayings and bits of wisdom were collected to make the lives of people just like us run a little more smoothly. Proverbs: Pathways to Wisdom explores the biblical book's well-known verses and prevalent themes in a manner that offers various interpretations, opening the way for us to see how they apply to our modern world. You'll learn about the authorship, genre, and historical setting for each of these verses, which will broaden your understanding and bring more meaning to familiar passages"--